Early developmental trajectories of expressive vocabulary and gesture production in a longitudinal cohort of Italian infants at high‐risk for Autism Spectrum Disorder. Issue 7 (1st March 2021) - Riva, Valentina; Caruso, Angela; Apicella, Fabio; Valeri, Giovanni; Vicari, Stefano; Molteni, Massimo; Scattoni, Maria Luisa
Abstract: Delays in language are a hallmark feature of Autism Spectrum Disorder (ASD). However, little is known about the predictive role of language developmental trajectories on ASD. The present study aimed at identifying early different language developmental profiles of infants at high familial risk for ASD (HR‐ASD) and testing their predictive role on ASD symptoms at 2 years. The role of gestures on socio‐communicative skills has also been explored. Trajectories of expressive vocabulary were investigated in 137 HR‐ASD infants at 12, 18, and, 24 months of age. Parents were requested to complete the Italian version of the MacArthur‐Bates Communicative Development Inventory and ASD symptoms were measured by ADOS‐2. Latent class growth analysis defined four trajectories: above average language development group (above‐average LD, 18.2%), normal language development group (NLD, 38.7%), late‐onset language development group (late‐onset LD, 11.7%), and a group of children with stable language delay (SLD, 31.4%). Results showed that the SLD group obtained higher communicative difficulties and restricted/repetitive behavior compared to the other groups. Examining early increase of produced gestures in the different language classes, we found fewer produced gestures between 12 and 18 months in the SLD group compared to the late‐onset LD group. The results identified clusters of HR infants who follow similar estimated trajectories based on individual differences in language development. These patterns of early language acquisition, together with produced gestures, may be predictive of later ASD symptoms and useful for planning prompt intervention. Lay Summary: Language/gesture deficits are hallmark features of Autism Spectrum Disorder (ASD), but the predictive role of communicative trajectories on ASD remains unclear. In a longitudinal Italian sample of infants at high familial risk for ASD (HR‐ASD), we tested if language trajectories and their link with gestures can predict ASD symptoms. We found four trajectories and HR infants with a stable language delay (SLD) trajectory showed more ASD symptoms later on. SLD infants produced fewer gestures compared to late‐onset language development group that show more typical communicative skills.